Role of Digital Technology and Data in Enhancing Competitiveness of Fashion Entrepreneurs in the Digital Era - Seprini; Yulfita (Journal of ICT Applications System, 2024)
Digital era has transformed the fashion industry, requiring entrepreneurs to adopt innovative digital marketing strategies to remain competitive. This study explores the role of digital technology and data in enhancing the competitiveness of fashion entrepreneurs. Through a qualitative approach with a case study method, data were collected from fashion entrepreneurs actively utilizing digital platforms such as social media, e-commerce, and websites. The findings reveal that integration of social media, websites, and e-commerce plays a crucial role in increasing consumer engagement, expanding market reach, and boosting sales growth. Additionally, use of customer data for personalized marketing enhances customer loyalty and improves business decision-making. Furthermore, adoption of advanced technologies such as Augmented Reality (AR), Virtual Reality (VR), and Artificial Intelligence (AI) provides unique shopping experiences, giving fashion businesses a competitive edge. This research highlights the importance of adaptive, data-driven, and technology-based digital marketing strategies in the success of fashion entrepreneurs. Implementing these strategies effectively will enable fashion businesses to strengthen their market position and achieve sustainable growth in the digital economy.